Testing the link between isoaspartate and Alzheimer's disease etiology. Issue 4 (4th August 2022) - Wang, Jijing; Guo, Cong; Meng, Zhaowei; Zwan, Marissa D.; Chen, Xin; Seelow, Sven; Lundström, Susanna L.; Rodin, Sergey; Teunissen, Charlotte E.; Zubarev, Roman A.
Abstract: Isoaspartate (isoAsp) is a damaging amino acid residue formed in proteins as a result of spontaneous deamidation. IsoAsp disrupts protein structures, making them prone to aggregation. Here we strengthened the link between isoAsp and Alzheimer's disease (AD) by novel approaches to isoAsp analysis in human serum albumin (HSA), the most abundant blood protein and a major carrier of amyloid beta (Aβ) and phosphorylated tau (p‐tau) in blood. We discovered a reduced amount of anti‐isoAsp antibodies ( P < 0.0001), an elevated isoAsp level in HSA ( P < 0.001), more HSA aggregates ( P < 0.0001), and increased levels of free Aβ ( P < 0.01) in AD blood compared to controls. We also found that deamidation significantly reduces HSA capacity to bind with Aβ and p‐tau ( P < 0.05). These suggest the presence in AD of a bottleneck in clearance of Aβ and p‐tau, leading to their increased concentrations in the brain and facilitating their aggregations there. Abstract : Elevated levels of isoAsp in blood HSA and reduced levels of antibodies against deamidated HSA pose risk of AD